2020
DOI: 10.1002/anie.202012456
|View full text |Cite
|
Sign up to set email alerts
|

Giant Optical Anisotropy in the UV‐Transparent 2D Nonlinear Optical Material Sc(IO3)2(NO3)

Abstract: Birefringence is a fundamental optical property for linear and nonlinear optical (NLO) materials. Thus far, it has proved to be very difficult to engineer large birefringence in optical crystals functioning in the UV region. Herein, we report the first 2D rare‐earth iodate–nitrate crystal Sc(IO3)2(NO3) (SINO), which is shown to exhibit giant optical anisotropy. Air‐stable SINO possesses a short UV absorption edge (298 nm), a strong NLO response (4.0 times that of benchmark KH2PO4) for the nitrate family, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 75 publications
1
95
0
Order By: Relevance
“…The NLO coefficient, birefringence, and absorption edge are the most critical optical parameters for NLO crystals [1, 3, 6–8] . How to achieve the modulation and enhancement of three pivotal parameters has always been a magnitude challenge for chemists and material scientists [9–14] . Previous studies have revealed that microscopic control‐mechanisms of second‐order NLO coefficient, birefringence, and absorption edge mainly originate from the geometric superposition of NLO‐active chromophores, the anisotropic response to incident light, and electron transition near the Fermi surface [1–3] .…”
Section: Introductionmentioning
confidence: 99%
“…The NLO coefficient, birefringence, and absorption edge are the most critical optical parameters for NLO crystals [1, 3, 6–8] . How to achieve the modulation and enhancement of three pivotal parameters has always been a magnitude challenge for chemists and material scientists [9–14] . Previous studies have revealed that microscopic control‐mechanisms of second‐order NLO coefficient, birefringence, and absorption edge mainly originate from the geometric superposition of NLO‐active chromophores, the anisotropic response to incident light, and electron transition near the Fermi surface [1–3] .…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optical (NLO) materials particularly working in the ultraviolet (UV) region play a significant role in producing coherent light of wavelengths below 300 nm. [1][2][3][4][5][6][7][8][9] During the past few decades, although many UV NLO materials, [10][11][12][13][14][15][16] such as β-BaB 2 O 4 (β-BBO), 10 LiB 3 O 5 (LBO), 11 and CsLiB 6 O 10 (CLBO), 12 have been discovered and some of them have been commercialized, these compounds suffer from some issues. For example, β-BBO exhibits a large birefringence (0.113@1064 nm) resulting in a large walk-off effect, 10 whereas the birefringence of LBO (0.0399@1064 nm) is too small to realize a wide phase-matching region.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is possible to precisely tailor the physical and chemical properties of crystalline materials by hybridizing anionic groups with different properties. This strategy afforded several excellent NLO compounds with mixed anionic groups, such as Bi 3 TeBO 9 , [2] B 2 S 2 O 9 , [3] Pb 2 (BO 3 )(NO 3 ), [4] Ba 3 (ZnB 5 O 10 )PO 4 , [5] Nb 2 O 3 (IO 3 ) 2 (SO 4 ), [6] Sc(IO 3 ) 2 (NO 3 ) [7] . However, borate‐iodate mixed NLO materials have never been reported due to the difficulty in synthesis, though the combination of diverse B‐O groups and (IO 3 ) − group with super large, microscopic second‐order NLO susceptibility may lead to novel NLO crystals with excellent optical properties.…”
Section: Figurementioning
confidence: 99%